A Practical Method to Design Reflector-Based Light-Emitting Diode Luminaire for General Lighting. (18th October 2018) - Yan, Jinren
Abstract : A reflector-based light-emitting diode (LED) luminaire structure that can achieve a large cut-off angle for general lighting is presented in this work. The proposed lighting unit mainly consists of a spherical reflector and a primary packaging lens that contains an aspheric surface and a spherical surface. The light rays emitted from the LED light source are well controlled by the spherical reflector and the aspheric surface of the lens for the purpose of obtaining a uniform illumination on the target surface. Both the ideal Lambertian LED and non-Lambertian LED light sources were employed to validate the proposed structure and the performance of the designed lighting units was analyzed by optical simulation. The results show that the light utilization efficiencies and the estimated uniformities are 92.96% and 91.11% for ideal Lambertian LED-based lighting unit and 93.31% and 91.64% for non-Lambertian LED-based lighting unit, respectively. Further analysis shows that the tolerances of horizontal, vertical, and rotational deviation of the both lighting units were about 2.0 mm, 1.0 mm, and 1.0°, respectively.